Integrated nutrient supply and varietal difference influence grain yield and yield related physio-morphological traits of durum wheat (Triticum turgidum L.) varieties under drought condition - Melash, Anteneh Agezew; Ábrahám, Éva Babett (Acta Agraria Debreceniensis, 2022)
The ever-growing world population entails an improvement in durum wheat grain yield to ensure an adequate food supply, which often gets impaired by several biotic and abiotic factors. Integrated nutrient management, such as nitrogen rate × foliar zinc × sulphur fertilization combined with durum wheat varieties were investigated in order to examine the dynamics of yield and yield related physio-morphological traits under drought conditions. The four durum wheat varieties, three-level of nutrient supply (i.e. control, sulphur, and zinc), and two nitrogen regimes (i.e. zero and 60 kg ha−1) were arranged in split-split plot design with three replications. Zinc and sulphur were applied as foliar fertilisation during the flag leaf stage, both at a rate of 3 and 4 liters ha-1, respectively. Results showed existence of genetic variability for grain yield, plant height, NDVI, SPAD and spike density. Foliar based application of zinc and sulphur at the latter stage improved the plant height. Nitrogen fertilized varieties with lower spike numbers showed to better yield formation. Co-fertilization of nitrogen and zinc improved grain yield of responsive varieties like Duragold by about 21.3%. Spikes per m2 were statistically insignificant for grain yield improvement. It could be inferred that the observed positive effect of sulphur, nitrogen and zinc application on physio-morphology and yield formation substantiates the need to include these essential nutrients in the cultivation system of durum wheat.